Seismic Performance of Steel Box Bridge Piers with Earthquake-Resilient Function - Haifeng Li; Wenwei Luo; Jun Luo (Advances in Civil Engineering)
A novel steel box bridge pier with replaceable energy dissipation wall plates at the base was proposed. After moderate earthquakes, the damaged energy dissipation wall plates and constraining steel plates on the two sides could be rapidly replaced, while the entire energy-dissipated column at the base can also be replaced after rare earthquakes. In this way, the seismic capacity of the new type of steel box bridge pier could be restored after earthquakes. For the purpose of discussing the seismic performance of this novel steel box-shaped bridge pier, the pseudostatic test and numerical simulation were performed. The results showed that the failure of the specimens in the pseudostatic tests occurred predominantly in the energy dissipation zone at the base. After replacing the damaged energy-dissipated column at the base, the seismic behavior of the proposed steel bridge pier can be recovered rapidly. Axial compression ratio is an important factor influencing the seismic behavior of the novel steel box bridge pier. The strength of the energy dissipation wall plates influences the novel steel box-shaped bridge pier’s bearing capacity and deformation capacity. Spacing between the horizontal stiffening ribs had little impact on the bearing capacity and deformation capacity of the proposed steel bridge pier. The larger the thickness of the energy dissipation wall plate, the higher the bearing capacity and deformation capacity of the steel box bridge pier. Finally, an empirical equation for the design of this novel steel bridge pier under cyclic loading was proposed.